(untitled) (Fiep Bulletin - online, 2014)
Although let us live the third millennium and the “war of the sex” has ahead lost of the affirmation of the woman as subject of rights and obligations, and consequently, its installation as protagonist in the process of historical construction of the contemporary, in unconscious the collective one of the societies, is possible to observe a direction of permanence of its “inferiority”. It wants in the sport, it wants in the politics, the religion and other sectors of the culture, the woman has consecrated its paper of prominence despite, the agencies of social communication if they charge to notify exactly that of dissimulate form, that the woman and the child still white frequent of are varied violence forms, manifest as in such a way symbolic.